Evaluation of Cerebral Vein Sinus Thrombosis in the Gynecology and Obstetrics Clinic: A Retrospective Study - Kavak, Salih; Batmaz, İbrahim; Şenocak, Ahmet; Halisçelik, Mesut; Gül, Yeliz; Şanlı, Cengiz; Kavak, Ebru Çelik (Kahramanmaras Sutcu Imam University, 2022)
Abstract Objective: Cerebral Vein Sinus Thrombosis (CVST) is a clinical condition that manifests itself with a wide variety of nonspecific symptoms and arises due to different etiologies. It is a rare disease that may not be easily diagnosed. Investigation of gynecological and obstetric causes in patients with Cerebral Vein Sinus Thrombosis (CVST). Material and Methods: Patients who admitted to Fırat University Medical Faculty Hospital between November 2010 and November 2020 with neurological complaints and were diagnosed with CVST in the evaluation performed and women who developed CVST due to obstetric/gynecological reasons were retrospectively analysed. The complaints, neuroradiological findings and treatments applied were determined from the records of the women. Descriptive statistics were used in the evaluation of the data. Results: At the time of the study period, 166 cases were diagnosed with CVST. One hundred and five of the cases were female (63.2%) and 61 were male (36.8%). It was found that CVST developed secondary to obstetric and gynecological causes in 15 cases (9%). The most common symptom was headache (80%) and the most common finding was papillary edema (20%), hemiparesis (13.3%) and hemiplegia (6.7%). Six cases (40%) included in the study were in the puerperal period. Of these, two cases (13.3%) gave birth by vaginally and four cases (26.7%) by caesarean. Five of the cases (33.3%) were pregnant. All of the pregnant women were in the third trimester of pregnancy. It was found that mastoiditis developed in one case (6.7%) and she delivered vaginally 4 months ago. One case (6.7%) had sinusitis and a family history of postpartum deep thrombosis was detected. Two cases (13.3%) were using combined oral contraceptives (OCS), and in one of them, MTHFR homozygous mutation and high homocysteine levels were detected. When all cases were evaluated, 7 cases (4.2%) had a diagnosis of hereditary thrombophilia. Conclusion: Obstetric and gynecological reasons, especially pregnancy, puerperal period and use of OCS, take up almost 10% of CVST cases and should be taken into consideration during the evaluation.

Özet Amaç: Serebral Ven Sinüs Trombozu (SVST) çok çeşitli ve nonspesifik semptomlarla kendini gösteren ve farklı etiyolojilere bağlı olarak ortaya çıkan klinik bir durumdur. Tanısı kolayca konulamayan nadir bir hastalıktır. Biz bu yazıda SVST gelişen olgularda, jinekolojik ve obstetrik nedenlerin araştırılmasını amaçladık. Gereç ve Yöntemler: Fırat Üniversitesi Tıp Fakültesi Hastanesi’ne Kasım 2010 ile Kasım 2020 tarihleri arasında nörolojik şikayetlerle başvuran, yapılan değerlendirmede SVST tanısı konulan olgular ile obstetrik/jinekolojik nedenlerle SVST gelişen kadınlar, retrospektif olarak incelendi. Kadınların başvuru şikâyetleri, nöroradyolojik bulguları ve uygulanan tedaviler kayıtlardan tespit edildi. Verilerin değerlendirmesinde tanımlayıcı istatistik kullanıldı. Bulgular: Çalışmanın yapıldığı dönemde 166 olguya SVST tanısı konuldu. Olguların 105’i kadın (%63.2) ve 61’i erkek (%36.8) idi. On beş olguda (% 9) obstetrik ve jinekolojik nedenlere sekonder SVST geliştiği tespit edildi. En sık semptom baş ağrısı (%80) ve en sık bulgu papil ödemi (%20) ile birlikte hemiparezi (%13.3) ve hemipleji (%6.7) olarak tespit edildi. Çalışmaya dâhil edilen altı olgu (%40) puerperal dönemde idi. Bunlardan iki olgu (%13.3) vajinal yolla, dört olgu (%26.7) ise sezaryenle doğum yapmıştı. Olgulardan beş tanesi (%33.3) gebe idi. Gebelerin tamamı gebeliğin 3. trimesterinde bulunuyordu. Bir olguda (%6.7) mastoidit geliştiği ve 4 ay öncesinde vajinal yolla doğum yaptığı tespit edildi. Bir olgunun puerperal dönemde olduğu ve eşlik eden sinüzit enfeksiyonu bulunduğu (%6.7), ayrıca aile öyküsünde postpartum derin ven trombozu varlığı tespit edildi. İki olgunun (%13.3) kombine oral kontraseptif (OKS) kullandığı, bunlardan birinde MTHFR homozigot mutasyon varlığı ve homosistein yüksekliği olduğu tespit edildi. Olguların tamamı değerlendirildiğinde 7 olguda (%4.2) kalıtsal trombofili tanısı mevcuttu. Sonuç: SVST olgularında gebelik, puerperal dönem ve OKS kullanımı başta olmak üzere, obstetrik ve jinekolojik nedenler %10’a yakın yer tutar ve değerlendirme sırasında göz önünde bulundurulmalıdır
Kadın Hastalıkları ve Doğum Kliniğinde Serebral Ven Sinüs Trombozu Gelişen Olguların Değerlendirilmesi: Retrospektif Çalışma
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi